Prototype of Car Washing Automation and Monitoring System Using Outseal PLC and Modbus HMI - Gusti Randa Affinda Putra; Ezwarsyah Ezwarsyah; Raihan Putri; Badriana Badriana; Rosdiana Rosdiana (Brilliance: Research of Artificial Intelligence, 2025)
Automation technology has significantly improved the efficiency of various sectors, including car washing services, which traditionally require intensive time and labor.This research aims to design and develop a prototype of an automatic car washing system using Outseal PLC and Modbus HMI to enhance the effectiveness and quality of car washing processes.The prototype integrates infrared proximity sensors, DC gearbox motors, DC pumps, DC fans, and a conveyor system controlled by a ladder diagram programmed through Outseal Studio. Wireless monitoring and control are enabled using the DT-06 WiFi module with Modbus TCP/IP protocol. Performance testing was conducted to evaluate system responsiveness, sensor accuracy, and the stability of wireless communication between the PLC and HMI.The system successfully automated all stages of the car washing process, including soap spraying, brushing, rinsing with clean water, and drying, achieving response times ranging from 0.14 to 0.3 seconds. Wireless communication remained stable up to a distance of 16 meters, and the infrared proximity sensors demonstrated high detection accuracy with an error margin of only 2–3.2%.The developed prototype effectively automates the car washing process with accurate detection and responsive control, operating reliably under testing conditions. This system is suitable for small-scale car washing operations and educational laboratory applications, with potential scalability for broader industrial implementation with additional development in advanced brush mechanisms and cloud-based monitoring integration.